Halogen-augmented pyrrole bisurea molecular tweezers for corrosion inhibition of Fe(110) surface: A first-principle investigation - Aymen S. Abu Hatab (23770563) (2025)
Iron rust imposes significant economic and industrial challenges, thus the need for the development of effective and environmentally friendly inhibitors. The research here leverages first-principles density function theory calculation (DFT) to investigate the potential of halogen-substituted pyrrole-based bisurea molecular tweezers as inhibitors of Fe(110) surface corrosion. Computations of electronic properties, tendencies toward adsorption, and interaction with molecules show that the chlorine substitution significantly enhances the effectiveness of corrosion inhibition. BUP-Cl features the lowest HOMO-LUMO gap (2.80 eV) after adsorption owing to its high polarizability, electron-donating properties, and synergistic effects with the iron surface. While the fluorine-substituted derivative (BUP-F) shows moderate improvement compared to the parent compound (BUP-H); however, steric and electronic restrictions hamper efficiency. The planar nature of the bisurea-pyrrole backbone fused with halogen substitutions enables strong chemisorption through π-back-donation, hydrogen bonding, and charge transfer. The findings highlight BUP-Cl as a promising inhibitor of rust, bringing important insights to the development of halogen-augmented environmentally friendly inhibitors using theoretical approaches. Other Information Published in: Surfaces and Interfaces License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.surfin.2025.108102